2019
DOI: 10.9734/jerr/2019/v7i216967
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hazards and Safety Practices in Food and Beverage Industry in Nigeria

Abstract: The assessment of safety hazards is fundamental to an effective risk management in any industry. Food and beverage production involves a variety of industrial processes with associated hazards. Effective safety practices are used to reduce workplace hazards and promote safety in the work environment. This paper evaluated safety hazards and safety practices in the food and beverage industry (FBI) in South-South, Nigeria. A structured questionnaire designed in accordance with World Health Organization standard w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Different factors were responsible for the respondents joining the chemical industry, however, job security and good working conditions were found to be the most attractive factors responsible for many of them joining the industry. This implies that most of respondents hope to secure their jobs up to retirement, this finding corroborated study by Afube et al [13].…”
Section: Respondents Characteristicssupporting
confidence: 89%
See 2 more Smart Citations
“…Different factors were responsible for the respondents joining the chemical industry, however, job security and good working conditions were found to be the most attractive factors responsible for many of them joining the industry. This implies that most of respondents hope to secure their jobs up to retirement, this finding corroborated study by Afube et al [13].…”
Section: Respondents Characteristicssupporting
confidence: 89%
“…Mann Kendall statistic was used to determine the level of agreement among the participants [21]. Cronbach's alpha coefficient formula [18,22] [13] to evaluate hazards and safety practices in food and beverage industry in Nigeria was adopted and used in this study to evaluate and rank the scores of respondents as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They seemed to be in unison in their perceptions that these practices have sufficiently catered to their safety needs. However, this information is in contrast with available evidence both in theory and practice (Otitolaiye, Abd Aziz, Munauwar, & Omer, 2021;Afube, Nwaogazie, & Ugbebor, 2019) and suggests the likelihood of either falsehood or disconnection from reality. Past studies (Wang et al, 2020;Kim et al, 2019;Subramaniam et al, 2016;Darwish et al, 2016) have shown that aside from the provision of HR practices, though important, the extent to which it satisfies needs weigh in the performance behaviour of employees.…”
Section: Discussioncontrasting
confidence: 58%